The significance of upright T wave in lead V1 in predicting myocardial ischemia A literature review - Fadi Kazahia Khir (17280745) (2021)
Chest pain is still representing one of the most common and serious presentations to the emergency department worldwide. ECG is a crucial tool in evaluating patients with chest pain; however, only around 50% of patients with acute coronary syndrome (ACS) will have a diagnostic ECG upon their presentation; the rest may either have a completely normal ECG or what is called nonspecific ST segment and T wave (NSSTTW) changes, hence it is essential to recognize the subtle ECG changes and know its significance. One of the ECG changes that can be easily missed is when the T wave in V1 is upright, especially when it is either a Tall Upright T wave (TTV1) or a New Tall Upright T-wave (NTTV1). Although upright T wave in lead V1 can be a normal variant, it has been linked in a few studies and observations to cardiovascular disease, especially myocardial ischemia. In this article, we are trying to highlight the importance of this subtle ECG change in predicting cardiovascular disease through a concise review of the available evidence on this topic. Other Information Published in: Journal of Electrocardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jelectrocard.2021.05.016